Causes and Consequences of Poliomavirus BK Infection in Kidney Transplant Recipients. (July 2018) - Flores, Isabel Perez; Gatius, Serena; Poma, Marisol; Cubillo, Beatriz Rodriguez; Delgado, Jesus; Procaccini, Fabio; Calvo, Natividad; de la Higuera, Maria Angeles Moreno; Culebras, Esther; Fructuoso, Ana Isabel Sanchez
Abstract : Objectives: 1) To investigate the risk factors for the development of polyomavirus BK infection (BKI). 2) Evaluate the impact of the same on graft survival and renal function at one year. Methods: We included 692 consecutive patients who received a kidney transplant in our unit during 2005-2015. Demographic data, pretransplant comorbidity, IC (leukocytes, lymphocytes, CD4, CD8 and CD4 / CD8 ratio), renal function [creatinine, glomerular filtration rate (GFR) by Cockroft-Gault and proteinuria], dose and type of immunosuppression a 1 were collected. 3, 6 and 12 months post-transplant and incidence of infections during the first year. Results: The prevalence of BKI in our unit has gone from 5 to 13% in recent years. It appears at 3.7 (2.7-8.2) months post-transplant, with a viral load of 90000 (2000-4450000) copies. We performed conversion to imTOR in 84% of the cases, with serum negativization in 90%. The risk factors related to viral replication in the univariate analysis were: severe UTI [RR = 4.19 (1.93-9.10), p = 0.020], treatment with thymoglobulin [RR = 2.45 (1.25-4.78), p = 0.007], time on dialysis>2 years [RR = 1.45 (1.16-1.80), p = 0.004], pretransplant DM [RR = 1.77 (0.99-3.54), p = 0.076], retransplantation [RR = 1.25 (0.94-1.29), p = 0.109], TCD4 lymphocytes <200/mcl in 3 months (RR = 2.02 (0.96-3.86), p = 0.060], TCD8 lymphocytes <200/mcl in 3 months [RR = 2.46 (1.09-5.54), p = 0.026]. In the multivariable analysis, only persists TCD8 lymphocytes <200/mcl in the third month [RR = 2.58 (1.10-6.04), p = 0.028] and treatment with thymoglobulin [RR = 2.09 (0.93-4.71), p = 0.074]. There were no differences in graft survival (92 vs 90%) or in renal function at one year (FG: 58 ± 16 vs 56 ± 18 ml / min, p = 0.419, proteinuria / creat 0.3 ± 0.5 vs 0.2 ± 0.2 mg / mg). Conclusions: The prevalence of BKI has increased in recent years in the kidney transplant population, but with an adequate management of immunosuppression and early conversion to imTOR may not negatively influence the results. The main risk factors for the development of active viral replication in our unit were the presence of CD8 + count <200/mcl.